2019
DOI: 10.1177/1010539519878361
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lower Urinary Tract Symptoms and Falls in Adults Males: Based on the Korean Community Health Survey

Abstract: This study aimed to investigate the correlation between lower urinary tract symptoms (LUTSs) and falls considering places where falls can occur in adult males. We analyzed 101 862 males in the 2011 Korean Community Health Survey. LUTSs were assessed using the International Prostate Symptom Score system. The rate of total and indoor falls significantly increased with the LUTS severity, respectively. After adjusting for age and other confounding variables, the odds ratios (ORs) for total falls were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In this context, a more comprehensive “multi-dimensional fall risk assessment” and intervention should be considered if the patient is determined to be at a high risk for falls. Fall-related risk factors include old age, past experience of falls, polypharmacy, impaired vision, walking disorders, muscle weakness, arthritis, osteoporosis, hypoglycemia, and cognitive dysfunction [ 115 , 116 ]. A multidimensional fall risk assessment of these various risk factors can also help determine appropriate interventions for problems based on the results of the assessment [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a more comprehensive “multi-dimensional fall risk assessment” and intervention should be considered if the patient is determined to be at a high risk for falls. Fall-related risk factors include old age, past experience of falls, polypharmacy, impaired vision, walking disorders, muscle weakness, arthritis, osteoporosis, hypoglycemia, and cognitive dysfunction [ 115 , 116 ]. A multidimensional fall risk assessment of these various risk factors can also help determine appropriate interventions for problems based on the results of the assessment [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fall-related risk factors include old age, past experience of falls, polypharmacy, impaired vision, walking disorders, muscle weakness, arthritis, osteoporosis, hypoglycemia, and cognitive dysfunction. 115,116) A multidimensional fall risk assessment of these various risk factors can also help determine appropriate interventions for problems based on the results of the assessment. 116) Regarding interventions for fall risk factors, exercise interventions have been reported to improve fall-associated indicators and to increase muscle strength, but did not reduce the actual incidence of falls.…”
Section: Cognitive Function (Recommendations 12 and 13)mentioning
confidence: 99%
“…Sporadic studies in Asian countries have compared this association. Studies in Korea have reported a link between LUTS and the risk of falls, possibly predisposing individuals to hip fractures; additionally, the employment of alpha-blockers for LUTS treatment was connected to an increased risk of hip fracture in elderly women [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Falls in the elderly occur frequently and are one of the most common causes of serious injury and injury-related death. [1][2][3][4][5] Approximately 30% of elderly people experience falls every year and they are a sign of frailty. 3,6 According to the increasing interest in the association of aging with frailty, many researchers have suggested the clinical implication of frailty in several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Falls in the elderly occur frequently and are one of the most common causes of serious injury and injury‐related death 1‐5 . Approximately 30% of elderly people experience falls every year and they are a sign of frailty 3,6 .…”
Section: Introductionmentioning
confidence: 99%